Comparison of biodiesel synthesis rates when being intensified with liquid extraction process - Zulhilmi, Khamis (2014)
Biodiesel has become more attractive recently because of its environmental benefits and the fact that it is is made from renewable resources. The cost biodiesel, however is the main hurdle to commercialization of the product. The used cooking oils are used as raw material, adaption of continuous transesterication process and recovery of high quality glycerol from biodiesel by-product (glycerol) are primary options to be consider to lower the cost of biodiesel. In transesterification, esters and glycerol will be formed by the separation of the vegetable oil. In this study, the characterization of the biodiesel synthesis will be made. Palm oil transesterification reaction with ethanol will be conducted with a set of oil-ethanol ratios under the counter current flow system by using the extractive reactor column so that the data obtained can be used to investigate the behaviour of the reacting fluid that flows counter currently with the reactant solvent (reaction rate study). Intensification of the biodiesel production process may offer significant capital and operating cost benefits due to fewer unit operations. In addition, the continuous removal of co-product glycerol from the reactive phase during transesterification promises higher biodiesel yield relative to conventional batch reactors. This paper presents the study of comparison synthesis rate of production biodiesel when intensified with liquid extraction process. This study also focusing on rate of reaction in production of biodiesel. Two type of reactor are been used in this experiment, batch reactor as an ideal reactor and continuous reactor, Extractive Reactor Column. Both reactor is using same reaction which is transesterification to produce biodiesel. To study the synthesis rate of the biodiesel, the experiment were conducted with different set of ratio in both reactor, 1:6, 1:12 and 1:24. The experiment is conducted at 45-60ْC this is the optimum temperature to produce biodiesel. For Extractive Reactor Column, it consists of 9 stage of Continuous Stirred Tank Reactor (CSTR) connected in series. The reactants were pump into the tank with different flow rate according to the desired ratio. The 0.02 mL sample is taken every 30 minutes, which is the reactant is enter every stages of the column and the sample is placed in a 1.5 mL of vial tube. The sample is then analysed using Gas Chromatographic- Flame Ionization Detector (GC-FID). From the data that been analyse, graph of triglyceride is plotted and graph of rate of reaction in plotted for every ratio and the compare the quantifies goodness of fit.